Antarctic sediment chronology by programmed-temperature pyrolysis: Methodology and data treatment - Rosenheim, B. E.; Day, M. B.; Domack, E.; Schrum, H.; Benthien, A.; Hayes, J. M. (Geochemistry Geophysics Geosystems, 2008)
We report a detailed programmed-temperature pyrolysis/ combustion methodology for radiocarbon (C-14) dating of Antarctic sub-ice shelf sediments. The method targets the autochthonous organic component in sediments that contain a distribution of acid-insoluble organic components from several sources of different ages. The approach has improved sediment chronology in organic-rich sediments proximal to Antarctic ice shelves by yielding maximum age constraints significantly younger than bulk radiocarbon dates from the same sediment horizons. The method proves adequate in determining isotope ratios of the pre-aged carbon end-member; however, the isotopic compositions of the low-temperature measurements indicate that no samples completely avoided mixing with some proportion of pre-aged organic material. Dating the unresolved but desired young end-member must rely on indirect methods, but a simple mixing model cannot be developed without knowledge of the sedimentation rate or comparable constraints. A mathematical approach allowing for multiple mixing components yields a maximum likelihood age, a first-order approximation of the relative proportion of the autochthonous component, and the temperature at which allochthonous carbon begins to volatilize and mix with the autochthonous component. It is likely that our estimation of the cutoff temperature will be improved with knowledge of the pyrolysis kinetics of the major components. Chronology is improved relative to bulk acid-insoluble organic material ages from nine temperature interval dates down to two, but incorporation of inherently more pre-aged carbon in the first division becomes more apparent with fewer and larger temperature intervals.
id: 1847; 284ON Times Cited:5 Cited References Count:27Y

Refining the radiocarbon dating of Antarctic marine sediments via stepped combustion - Schrum, H.; Hayes, J.; Domack, E. (Eps Trans AGU, 2006)
id: 702